2020
DOI: 10.2174/1568009620666200619123725
|View full text |Cite
|
Sign up to set email alerts
|

The Roles of Alternative Splicing in Tumor-immune Cell Interactions

Abstract: : Alternative splicing (AS) plays a significant role in the hallmarks of cancer and can provide neoantigens for immunotherapy. Here, we summarize recent advances in immune system associated tumor specific-antigens (TSAs) produced by AS. We further discuss the regulating mechanisms involved in AS-mediated innate and adaptive immune responses and the anti-tumoral and pro-tumoral roles in different types of cancer. For example, ULBP1_RI, MLL5△21spe, NKp44-1△5, MHC-I△7, CD200S△1, 2, PVR α/β/γ/δ and IL-33 variants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 113 publications
(123 reference statements)
0
12
0
Order By: Relevance
“…Previous studies have shown that alternative splicing plays an important role in cancer immunity. 48 , 49 , 50 , 51 The immunogenic epitope in tumor cells is constitutively spliced out, which made the tumor cells cloud not be recognized by T‐cell receptor engineered T cells. 7 Therefore, whether the risk score could complement with immune score to better evaluate the efficacy and prognosis of immunotherapy still needs more in‐depth analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that alternative splicing plays an important role in cancer immunity. 48 , 49 , 50 , 51 The immunogenic epitope in tumor cells is constitutively spliced out, which made the tumor cells cloud not be recognized by T‐cell receptor engineered T cells. 7 Therefore, whether the risk score could complement with immune score to better evaluate the efficacy and prognosis of immunotherapy still needs more in‐depth analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have reported that aberrant AS events are involved in a variety of tumor processes, including immune destruction [ 49 , 50 ]. Neoepitopes derived from aberrant AS events are recognized by T lymphocytes to induce antitumor immune responses [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…AS regulates immune responses across a variety of conditions ( 17 ). The AS events of specific genes could influence tumor growth between tumor-immune cell interactions ( 18 ). Studies have investigated how AS serves to modulate lymphocyte activity ( 19 ).…”
Section: Discussionmentioning
confidence: 99%